If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 3(3x + -17) = -76 Reorder the terms: -4x + 3(-17 + 3x) = -76 -4x + (-17 * 3 + 3x * 3) = -76 -4x + (-51 + 9x) = -76 Reorder the terms: -51 + -4x + 9x = -76 Combine like terms: -4x + 9x = 5x -51 + 5x = -76 Solving -51 + 5x = -76 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '51' to each side of the equation. -51 + 51 + 5x = -76 + 51 Combine like terms: -51 + 51 = 0 0 + 5x = -76 + 51 5x = -76 + 51 Combine like terms: -76 + 51 = -25 5x = -25 Divide each side by '5'. x = -5 Simplifying x = -5
| 4b-4-11b-6= | | c-2/2+12=36 | | 0=0.001(0.732x^2+15.417x+605.738) | | 900+900+3x=700+500+9z | | x+1=7x | | 5x+12=4x+8 | | 49-49+81= | | 5x-2(6x+12)=53 | | 6x-3(6x-10)=162 | | x+10/2=42 | | 2x-2(2x-3)=-6 | | 2(x+4)=5xw+1 | | -3+-3+-2+-2+-2+-2+-1+-1+0+0+1+1+3+4= | | 4=(2+x)/2 | | 10j-10=3j-5 | | 7(x-3)=-4 | | -1=(8+x)/2 | | -4y+8=-2(4y+8) | | 7x+-1=4x+3 | | 0.4x+0.2(30)=0.3(x+30) | | -5x-7(-3x+9)=113 | | 9(z-3)=2(z+1) | | 4x+23=12x-76 | | 3y^2-3y-22=0 | | 5t-t-7=3t-5 | | 0.5x+0.4(30)=0.3(x+30) | | 7m-5=2m-20 | | 11x-31=6x+14 | | 25c^2-70c+49=0 | | 8k+5=4k+13 | | -9y-10=-5y+14 | | 1.5x+1.3=.25x-1.16 |